Pengaruh Paket Menu Sehat terhadap Peningkatan Kadar Hb Remaja Putri - Purwati, Purwati; Rohayati, Rohayati (Politeknik Kesehatan Tanjung Karang, 2019)
Female teenager is one of the vulnerable groups to suffer anemia. Anemia prevalence of female teenager belongs to a public health problem. The objective of this research was to find out the influences of the healthy menu to female teenager Hb level improvement in the Roudhlatul Qur’an Islamic Boarding School in Metro in 2018. This research used quasi-experiment pretest and posttest with control group design by comparing two groups with the intervention of healthy menu package administration to a treatment group and giving no treatment to control group. The population was 60 female teenagers in Roudhlatul Qur’an Islamic Boarding School. Data were collected by conducting Hb examination by using Haemock before and after treatment. Data were processed and analyzed by using an independent t-test. The average result of Hb level of respondents having health menu package treatment was 14.76gr% with standard of deviation of 1.37 and 13.56gr% in control group respondent with a standard of deviation of 1.05. The statistic test result derived p-value 0.000 with an alpha of 5%, and this indicated that there was a significant difference in Hb level average between treatment group and control group. There is an effect of healthy menu packages on Improvement Young Women HB Levels.